8 - The Western Super-Powers and the Liberation Struggle in Africa: The Politics of Imperialism, Domination and Resistance, 1948-1980s - Sifiso Mxolisi Ndlovu (Afrika Zamani, 2022)
Controlling South Africa during the Cold War era was geostrategic to the West- ern super powers because of its 1,900-mile coastline with harbours at Durban, East London, Port Elizabeth, Cape Town and Walvis Bay (a seaport in the then South West Africa, now Namibia). Being the southernmost country on the Af- rican continent, South Africa abuts on both the Indian and the Atlantic Oceans and its fascist leaders vociferously pledged to ‘defend the free world from the communist threat’ during the Cold War era. Thus, apartheid South Africa played a vital role in the global strategy of imperialism led by Western super powers such as the United States of America and United Kingdom to make the Indian Ocean area a region for their dominance and total control. South Africa was thus regarded as a ‘second Gibraltar’ or ‘gatekeeper’ to the Indian and Atlantic Oceans. This article is about imperial interventions in the African continent spearheaded by Western super powers, and the pivotal role of apartheid South Africa in this regard. It also discusses the actions of African countries whose leaders acted in solidarity with the apartheid regime which had divisive for- eign policy. But those African leaders who acted in solidarity with the racist South African government represented a minority group vigorously opposed by a majority of Organisation of African Unity member states and the African National Congress (ANC).